Focal Adhesions Require Catalytic Activity of Src Family Kinases To Mediate Integrin-Matrix Adhesion - Li, Leiming (American Society for Microbiology, 2002)
Members of the Src family of tyrosine kinases function to phosphorylate focal adhesion (FA) proteins. To explore the overlapping functions of Src kinases, we have targeted Csk, a negative regulator of the Src family, to FA structures. Expression of FA-targeted Csk (FA-Csk) effectively reduced the active form (nonphosphorylated at the C-terminal regulatory tyrosine) of Src members in the cell. We found that fibroblasts expressing FA-Csk lost integrin-mediated adhesion. Activated Src (SrcY529F) as well as activation of putative Src signaling mediators (Fak, Cas, Crk/CrkL, C3G, and Rap1) blocked the effect of FA-Csk in a manner dependent on Rap1. SrcY529F also inhibited activated Ras-induced cell detachment but failed to rescue detachment caused by an activated mutant of Raf1 (Raf-BXB) that Rap1 cannot inhibit. Although normal spreading onto fibronectin was restored by the β(1) integrin affinity-activating antibody TS2/16 in cells expressing FA-Csk or Raf-BXB, FAs were lost in these cells. On the other hand, Rap1 activation could restore FAs in cells expressing FA-Csk. Activation of the executioner caspase, caspase 3, is essential for many forms of apoptosis. While a caspase 3 inhibitor (Z-DEVD-FMK) inhibited cell detachment triggered by activation of caspase 8, this inhibitor had no effect on cell detachment caused by FA-Csk. Likewise, overexpression of an activated Akt made cells resistant to the effect of caspase 8 activation, but not to the effect of FA-Csk. It is therefore likely that the primary cause of cell rounding and detachment induced by FA-Csk involves dysfunction of FAs rather than caspase-mediated apoptosis that may result from possible loss of survival signals mediated by Src family kinases. We suggest that endogenous Src family kinases are essential for FAs through activation of Rap1 in fibroblasts.